684 Use of Overnight Pulse Oximetry and STBUR Questionnaire for Paediatric OSA In A District General Setting. (4th May 2021) - Rogers, A; Fraser, L; Geary, T
Abstract: Introduction: Overnight pulse oximetry (OPO) is often used to support the diagnosis of obstructive sleep apnoea (OSA) and stratify risk of peri-operative breathing difficulties in children undergoing adenotonsillectomy for OSA. Our objective was to audit our indications for OPO and the impact on subsequent ENT management. We sought to assess the correlation of STBUR (Snoring, Troubled-breathing, Unrefreshed Questionnaire) score with OPO values in these patients. Method: Retrospective review of 32 OPO reports over a 7-month period. Data collected included age, weight, indication, mean spO2, number of dips >4%, outcome and STBUR score. Results: The commonest indication (19) for OPO was to assess severity of OSA in children <3 or those with significant comorbidity to determine best setting for surgery; 50% were ultimately managed in a tertiary centre. 10 children underwent OPO due to diagnostic uncertainty but significant parental concern; all studies normal and parents reassured. STBUR score correlated poorly with number of dips >4% (R = 0.0109) and mean nadir >4% (R = 0.0031) Weight poorly recorded (19%). Conclusions: Referrals were generally appropriate and influenced management in all cases. STBUR scores insufficiently sensitive to stratify severity of OSA. New protocol developed.